Disentangling the Effects of Tillage Timing and Weather on Weed Community Assembly - Stéphane Cordeau; Richard G. Smith; Eric R. Gallandt; Bryan Brown; Paul Salon; Antonio DiTommaso; Matthew R. Ryan (Agriculture, 2017)
The effect of tillage timing on weed community assembly was assessed at four locations in the Northeastern United States by tilling the soil every two weeks from April to September and quantifying the emerged weed community six weeks after each tillage event. Variance partitioning analysis was used to test the relative importance of tillage timing and weather on weed community assembly (106 weed species). At a regional scale, site (75.5% of the explained inertia)—and to a lesser extent, timing—of tillage (18.3%), along with weather (18.1%), shaped weed communities. At a local scale, the timing of tillage explained approximately 50% of the weed community variability. The effect of tillage timing, after partitioning out the effect of weather variables, remained significant at all locations. Weather conditions, mainly growing degree days, but also precipitation occurring before tillage, were important factors and could improve our ability to predict the impact of tillage timing on weed community assemblages. Our findings illustrate the role of disturbance timing on weed communities, and can be used to improve the timing of weed control practices and to maximize their efficacy.